AN EVALUATION OF TEXTURE MANIPULATIONS TO INCREASE SWALLOWING. Issue 2 (4th April 2013) - Kadey, Heather; Piazza, Cathleen C.; Rivas, Kristi M.; Zeleny, Jason
Abstract The purpose of the current investigation was to identify an appropriate texture for initial treatment of 1 child's feeding problem. Variability in mouth clean (a product measure of swallowing) during a texture assessment suggested that individual pureed foods differentially affected feeding behavior. A single‐food assessment identified individual problematic foods. We used the results of these assessments to inform treatment, resulting in high levels of mouth clean across foods.